Implementation of the MIMHa Interactive Programme on the Development of Students' Spiritual and Social Attitudes at MI Miftahul Huda Bandung - Alfirdausi, Andru; Wahyu Hidayat (Sekolah Tinggi Agama Islam Darul Qur'an Payakumbuh, 2025)
This research explores the development of students' spiritual and social attitudes at MI Miftahul Huda Bandung through the MIMHa Interactive programme. The programme aims to enhance students’ awareness of worship, understanding of Islamic values, and social skills using an interactive learning approach that integrates technology and student-centred teaching methods. The study examines the design, implementation strategies, and the programme’s impact on students’ spiritual and social character development. Findings indicate that the MIMHa Interactive programme effectively creates an engaging and participatory learning environment, which positively influences students’ spiritual and social behaviours. However, several challenges were identified, such as limited school facilities and a lack of parental support, which hinder the optimal implementation of the programme. The study provides insights into the key factors that contribute to the programme's success and offers recommendations for improving similar educational initiatives. It is expected that these findings can serve as a reference for other educational institutions aiming to integrate technology with character education based on spiritual and social values in a more effective and sustainable way.